Development and rapid rollout of The QUiPP App Toolkit for women who arrive in threatened preterm labour - Carlisle, Naomi (BMJ Open Qual, 2021)
BACKGROUND: Often the first opportunity for clinicians to assess risk of preterm birth is when women present with threatened preterm labour symptoms (such as period-like pain, tightening’s or back ache). However, threatened preterm labour symptoms are not a strong predictor of imminent birth. Clinicians are then faced with a complex clinical dilemma, the need to ameliorate the consequences of preterm birth requires consideration with the side-effects and costs. The QUiPP app is a validated app which can aid clinicians when they triage a women who is in threatened preterm labour. AIM: Our aim was to produce a toolkit to promote a best practice pathway for women who arrive in threatened preterm labour. METHODS: We worked with two hospitals in South London. This included the aid of a toolkit midwife at each hospital. We also undertook stakeholder focus groups and worked with two Maternity Voice Partnership groups to ensure a diverse range of voices was heard in the toolkit development. While we aimed to produce the toolkit in September 2020, we rapidly rolled out and produced the first version of the toolkit in April 2020 due to COVID-19. As the QUiPP app can reduce admissions and hospital transfers, there was a need to enable all hospitals in England to have access to the toolkit as soon as possible. RESULTS: While the rapid rollout of The QUiPP App Toolkit due to COVID-19 was not planned, it has demonstrated that toolkits to improve clinical practice can be produced promptly. Through actively welcoming continued feedback meant the initial version of the toolkit could be continually and iteratively refined. The toolkit has been recommended nationally, with National Health Service England recommending the app and toolkit in their COVID-19 update to the Saving Babies Lives Care Bundle and in the British Association of Perinatal Medicine Antenatal Optimisation Toolkit.